2019
DOI: 10.1111/jsr.12850
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in electroencephalogram spectral power with varying apnea duration in older adults

Abstract: Sleep apnea elicits brain and physiological changes and its duration varies across the night. This study investigates the changes in the relative powers in electroencephalogram (EEG) frequency bands before and at apnea termination and as a function of apnea duration. The analysis was performed on 30 sleep records (375 apnea events) of older adults diagnosed with sleep apnea. Power spectral analysis centered on two 10‐s EEG epochs, before apnea termination (BAT) and after apnea termination (AAT), for each apnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, the EEG signals routinely collected by PSG have not been fully utilized. There have been a number of studies that have analyzed the EEG power of OSA, 17 , 18 but the results of the studies were not consistent. One of the reasons is that there was no unified standard for the sampling method of EEG signals or the definition of the frequency spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…However, the EEG signals routinely collected by PSG have not been fully utilized. There have been a number of studies that have analyzed the EEG power of OSA, 17 , 18 but the results of the studies were not consistent. One of the reasons is that there was no unified standard for the sampling method of EEG signals or the definition of the frequency spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in opposition to the findings of Dingli et al [13], who observed an increase in relative post-event delta power during NREM sleep; however, this increase was observed only when there was no visible EEG arousal at event termination. Relative theta (4-8 Hz) power has also been observed both to decrease [13], [14] and increase [12] after apnea and hypopnea termination. Relative alpha (8)(9)(10)(11)(12) and sigma (12)(13)(14)(15)(16) powers are known to increase after apnea and hypopnea termination in Stage R sleep [12], [14].…”
Section: Introductionmentioning
confidence: 92%
“…Relative theta (4-8 Hz) power has also been observed both to decrease [13], [14] and increase [12] after apnea and hypopnea termination. Relative alpha (8)(9)(10)(11)(12) and sigma (12)(13)(14)(15)(16) powers are known to increase after apnea and hypopnea termination in Stage R sleep [12], [14]. This increase has also been observed in NREM sleep when respiratory events were terminated by arousals [13].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations